The Effect of Motivation on Work Achievement at PT. Tjipta Rimba Djaja Plywood Factory - Jon Hendri Purba (East Asian Journal of Multidisciplinary Research, 2022)
The purpose of this study was to determine and analyze the effect of intrinsic motivation and extrinsic motivation on work performance. The number of research samples is active employees of PT. Tjipta Rimba Djaja Plywood Factory in 2020 has as many as 79 people. Methods of data analysis using multiple linear regression. The results showed that intrinsic motivation had a positive and significant effect on work performance, with a t-count of 4,464> a t-table of 1,991 or a significance value of 0.000 <α (0.05). Extrinsic motivation has a positive and significant effect on work performance, with a t-count value of 3.845> a t-table value of 1.991 or a significance value of 0.000 <α (0.05). Intrinsic motivation and extrinsic motivation have a positive and significant effect on work performance, with a Fount value of 41.026> F-table value of 3.120 or a significance value of 0.000 <α (0.05).